Birds and bats diverge in the qualitative and quantitative components of seed dispersal of a pioneer tree - Jacomassa, Fabio Andre F.; Pizo, Marco Aurelio [UNESP] (Gauthier-villars/editions Elsevier, 2010)
Although the overlap in fruit diet between birds and bats is low, they sometimes consume and compete for fruits of the same plant species. What is poorly known is how birds and bats compare with each other in relation to the effectiveness of seed dispersal. In this paper we contrasted birds and bats in relation to quantitative (the amount of fruits removed from plants) and qualitative (germination performance of seeds) components of the seed dispersal of Solanum granuloso-leprosum, a pioneer, small-seeded tree of open areas and forest edges in south Brazil. We tagged fruits on the plants and monitored their removal by day and night. We compared the final percent of germination and speed of germination of seeds ingested by birds and bats with non-ingested, control seeds. While bats removed more fruits than birds, performing better in the quantitative component, birds improved the germination performance of seeds, an aspect of the qualitative component of seed dispersal effectiveness. Although bats are more likely to deposit seeds in highly disturbed sites that favor the recruitment of pioneer plant species, birds frequent forest edges, which is also suitable habitat for S. granuloso-leprosum, We concluded that birds and bats are not 'redundant' seed dispersers for S. granuloso-leprosum because in conjunction they may enhance its recruitment by diversifying the microsites where seeds are deposited, performing in addition different ecological functions in terms of quantity and quality of dispersal. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Atlantic forest; Brazil; Fruit removal; Functional groups; Germination success; Speed of germination